Immunogenicity of COVID-19 mRNA Vaccines in Pregnant and Lactating Women. Issue 1 (23rd March 2022) - Collier, A.Y.; McMahan, K.; Yu, J.; Tostanoski, L.H.; Aguayo, R.; Ansel, J.; Chandrashekar, A.; Patel, S.; Apraku Bondzie, E.; Sellers, D.; Barrett, J.; Sanborn, O.; et al.
Abstract : ( JAMA . 2021;325:2370–2380. doi-10.1001/jama2021.7563) Pregnant women are at a greater risk of severe complications from symptomatic COVID-19, including ICU admission, needing mechanical ventilation, and death compared with their nonpregnant peers. Similarly, women who contract influenza and other viruses during pregnancy often have more severe illnesses as pregnancy reduces immune system effectiveness to prevent an immune system response to foreign DNA in a fetus. Women are encouraged to receive influenza and pertussis vaccines during pregnancy. In addition to protecting the mother from complications from these viruses while pregnant, studies have shown the baby also carries antibodies to prevent these viral infections after birth while it is too young to yet receive these vaccinations. A patient biorepository study from Beth Isreal Deaconess Medical Center investigated if babies of pregnant or lactating mothers who received a COVID-19 vaccine also carried antibodies to prevent this new virus. In addition the number of antibodies in babies born to women who had contracted COVID-19 while pregnant was compared to antibodies of babies whose mothers had only received a vaccine.